Bacteriophage Therapy for Critical Infections Related to Cardiothoracic Surgery - Evgenii Rubalskii; Stefan Ruemke; Christina Salmoukas; Erin C. Boyle; Gregor Warnecke; Igor Tudorache; Malakh Shrestha; Jan D. Schmitto; Andreas Martens; Sebastian V. Rojas; Stefan Ziesing; Svetlana Bochkareva; et al. (MDPI AG, 2020)
(1) Objective: Bacterial resistance to conventional antibiotic therapy is an increasingly significant worldwide challenge to human health. The objective is to evaluate whether bacteriophage therapy could complement or be a viable alternative to conventional antibiotic therapy in critical cases of bacterial infection related to cardiothoracic surgery. (2) Methods: Since September 2015, eight patients with multi-drug resistant or especially recalcitrant Staphylococcus aureus, Enterococcus faecium, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli infections were treated with bacteriophage preparations as a therapy of last resort according to Article 37 of the Declaration of Helsinki. Patients had infections associated with immunosuppression after organ transplantation or had infections of vascular grafts, implanted medical devices, and surgical wounds. Individualized phage preparations were administered locally, orally, or via inhalation for different durations depending on the case. All patients remained on conventional antibiotics during bacteriophage treatment. (3) Results: Patients ranged in age from 13 to 66 years old (average 48.5 ± 16.7) with seven males and one female. Eradication of target bacteria was reached in seven of eight patients. No severe adverse side effects were observed. (4) Conclusions: Phage therapy can effectively treat bacterial infections related to cardiothoracic surgery when conventional antibiotic therapy fails.